2016
DOI: 10.1088/2040-8978/18/5/055006
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured SERS substrates produced by nanosphere lithography and plastic deformation through direct peel-off on soft matter

Abstract: We present a novel fragmented-film surface-enhanced Raman scattering (SERS) substrate produced by nanosphere lithography and direct peel-off for SERS efficacy enhancement. The 2D hexagonally close-packed polystyrene nanospheres on the polydimethylsilozane (PDMS) substrate are covered with silver film and then directly peeled off using sticky tape. During the peel-off process, the pulling force induces the stretch and contraction of the PDMS substrate and causes fracture of the 2D triangular silver film. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…The exchange of energy involves the gain or loss of vibrational energy by a molecule as incident photons from a visible laser shift to lower or higher energy states. Surface-enhanced Raman scattering (SERS) [111,[119][120][121][122] involves the amplification of Raman scattering signals by SPs on a metallic surface with high charge carrier density. Brooks et al conducted an in-depth review of Raman spectroscopy applications for understanding plasmon-mediated photocatalysis [20].…”
Section: Optical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exchange of energy involves the gain or loss of vibrational energy by a molecule as incident photons from a visible laser shift to lower or higher energy states. Surface-enhanced Raman scattering (SERS) [111,[119][120][121][122] involves the amplification of Raman scattering signals by SPs on a metallic surface with high charge carrier density. Brooks et al conducted an in-depth review of Raman spectroscopy applications for understanding plasmon-mediated photocatalysis [20].…”
Section: Optical Measurementsmentioning
confidence: 99%
“…Energy transformation in plasmonic material sensing (i.e., chemical and biosensing [136][137][138][139][140][141] and SERS [119][120][121][122]) resembles that in plasmonic photocatalytic reactions. Therefore, methods of obtaining larger or enhanced signal readings in plasmonic sensing resemble to a higher enhanced processing efficiency in plasmonic photocatalytic reactions.…”
Section: Optical Measurementsmentioning
confidence: 99%
“…Plasmon resonances occur, and these resonances are dependent on the geometrical structures of the metal nanostructures, like the localized surface plasmon resonance (SPR) and gap plasmon resonance (GPR) of metallic nanorods [1][2][3][4]. Studies have reported the potential use of these resonances, e.g., plasmonic sensors [5,6], infrared band filters [7,8], surface-enhanced Raman scattering (SERS) substrates [9,10], and heat radiation/absorption manipulation [11]. The advances in nanofabrication technologies [12,13] have a significant impact in promoting the use of plasmonic nanorod arrays as SPR sensors [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…back in 1982 and pioneered by Van Duyne’s group2345 in the late 1990 s, has come a long way by manifesting itself as a fast, low cost and high throughput nanofabrication method to produce regular arrays of nanostructures6. NSL can be divided broadly into three steps: colloidal mask generation, diameter control and lift-off.…”
mentioning
confidence: 99%
“…Lastly, the PNs are etched away in a solvent by lift-off, leaving onto the substrate, regular arrays of the material deposited. Nanoparticle arrays produced by this method are often used as surface enhanced Raman scattering substrates6 for biological and chemical sensors as well as catalysts for the growth of one-dimensional nanostructures1415161718. Industry has pushed researchers far enough to implement and make the user-friendly spin-coating process viable and able to produce films with controlled thicknesses over large areas.…”
mentioning
confidence: 99%